Formulation and development and evaluation of microencapsulated suspension of ofloxacin - Ch, Saibabu; M, Swapna (International Journal of Indigenous Herbs and Drugs, 2021)
The present work is to formulation and evaluation of Ofloxacin of microencapsulated suspension by using solvent evaporation method. The Preparation contains six formulations of suspensions with 2 different polymers with different concentrations as Ofloxacin resinate + HPMC, Ofloxacin resinate + Carbopol 934. The prepared batches of Ofloxacin microencapsulated suspension were evaluated for the pH, viscosity, sedimentation volume; density, drug content and antibacterial activity of all the six formulations were performed. Formulations F-3, F-6 gave better sustained release and antibacterial activity. Comparative study of F-3, F-6 with marketed product reveal the F-3 is best fitted formulation for preparation of microencapsulated suspension.